Deciphering the Virus Signal Within the Marine Dissolved Organic Matter Pool - Heinrichs, Mara E.; Heyerhoff, Benedikt; Arslan-Gatz, Berin S.; Seidel, Michael; Niggemann, Jutta; Engelen, Bert (Frontiers in Microbiology, 2022)
Viruses are ubiquitously distributed in the marine environment, influencing microbial population dynamics and biogeochemical cycles on a large scale. Due to their small size, they fall into the oceanographic size-class definition of dissolved organic matter (DOM; <0.7 µm). The purpose of our study was to investigate if there is a detectable imprint of virus particles in natural DOM following standard sample preparation and molecular analysis routines using ultrahigh-resolution mass spectrometry (FT-ICR-MS). Therefore, we tested if a molecular signature deriving from virus particles can be detected in the DOM fingerprint of a bacterial culture upon prophage induction and of seawater containing the natural microbial community. Interestingly, the virus-mediated lysate of the infected bacterial culture differed from the cell material of a physically disrupted control culture in its molecular composition. Overall, a small subset of DOM compounds correlated significantly with virus abundances in the bacterial culture setup, accounting for <1% of the detected molecular formulae and <2% of the total signal intensity of the DOM dataset. These were phosphorus- and nitrogen-containing compounds and they were partially also detected in DOM samples from other studies that included high virus abundances. While some of these formulae matched with typical biomolecules that are constituents of viruses, others matched with bacterial cell wall components. Thus, the identified DOM molecular formulae were probably not solely derived from virus particles but were partially also derived from processes such as the virus-mediated bacterial cell lysis. Our results indicate that a virus-derived DOM signature is part of the natural DOM and barely detectable within the analytical window of ultrahigh-resolution mass spectrometry when a high natural background is present.